The Effect of Cabbage (Brassica oleracea var. capitata L.) Extract on Macrophage and Blood Vessel Counts in Clean Wound Tissue of Male Rats (Rattus norvegicus) - Tsania, Nidya Ulfana; Sandhika, Willy; , Sawitri (Folia Medica Indonesiana, 2023)
Highlights : • Cabbage extract application accelerates wound healing and has anti-inflammatory effect. • Cabbage extract serves as an affordable source material for wound healing and anti-inflammation. Abstract Cabbage is a widely consumed vegetable known for its health benefits due to its rich nutrients and phytochemicals, especially phenolic compounds, which are known to have potent anti-inflammatory and antioxidant effects. This study aimed to investigate the effects of cabbage extract on wound healing by observing inflammatory responses in wound tissue. A total of 24 male rats were divided into four groups, with six rats in each group. The experiment was conducted for five days by administering cabbage extract to the treatment group and distilled water to the control group. Skin wound tissues were collected from all rats for histological observation by counting the number of macrophages and blood vessels. The results of the observation were analyzed statistically using an independent sample t-test with p<0.05. The results showed that the number of macrophages and blood vessels in the treatment group was significantly higher than the control group on the third day and significantly lower on the fifth day. In conclusion, the administration of cabbage extract can accelerate the inflammatory and proliferative phases of wound healing by promoting the migration of cells, including macrophages, resulting in accelerated angiogenesis. In addition, the decreased number of macrophages and blood vessels during the proliferative phase showed that the healing phase had reached a more advanced stage.